2012
DOI: 10.1089/ten.tea.2010.0414
|View full text |Cite
|
Sign up to set email alerts
|

Response of a Preosteoblastic Cell Line to Cyclic Tensile Stress Conditioning and Growth Factors for Bone Tissue Engineering

Abstract: Bone regeneration can be accelerated by utilizing mechanical stress and growth factors (GFs). However, a limited understanding exists regarding the response of preosteoblasts to tensile stress alone or with GFs. We measured cell proliferation and expression of heat-shock proteins (HSPs) and other bone-related proteins by preosteoblasts following cyclic tensile stress (1%-10% magnitude) alone or in combination with bone morphogenetic protein-2 (BMP-2) and transforming growth factor-b1 (TGF-b1). Tensile stress (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 86 publications
3
11
0
Order By: Relevance
“…Parts of the specimens were subjected to HE [15] and Masson [16] staining, and the ossification results were observed after fixation and embedding.…”
Section: Methodsmentioning
confidence: 99%
“…Parts of the specimens were subjected to HE [15] and Masson [16] staining, and the ossification results were observed after fixation and embedding.…”
Section: Methodsmentioning
confidence: 99%
“…However, heating (for 8 minutes) alone induced mRNA expression of OCN (3.8 RFI), OPN (1.8 RFI), and OPG (2.1 RFI) genes at 8-hour postheating in our previous study [27]. Furthermore, in our prior work [43], we observed significant OPG secretion in response to 5% tensile stress preconditioning, comparable to the current study employing 3% tension, suggesting that OPG can be upregulated by tension, but not significantly by thermal stress. The discrepancy may be caused by culturing cells on a type I collagen-coated flexible substrate and the use of a different FBS concentration in the osteogenic culture media between these two studies.…”
Section: Resultsmentioning
confidence: 93%
“…[13][14][15]19,44 Previous studies with human periodontal ligament stem cells, preosteoblasts, and osteoblasts have also reported that tensile strain induces osteogenesis and ECM formation. [56][57][58] We have also previously found that 10% cyclic tensile strain induces the upregulation of proinflammatory cytokine regulators: SOCS3 and IL1RN, and angiogenic factors: FGF2, VEGFA, and MMP2 in hASC undergoing osteogenic differentiation. 19 Findings from the current study indicate that upregulation of VEGF in response to 10% cyclic tensile strain is consistent in both hASC and hMSC.…”
mentioning
confidence: 77%